Influência da morfologia na remoção seletiva de cianobactérias em três estações de tratamento de água via diferentes tecnologias de filtração - Lopes, Ismael Keslley Carloto (2018)
Considering the public health threats caused by secondary metabolites produced by public water supply-dwelling cyanobacteria, it is of critical importance to investigate the fate of those microorganisms through the unit operations which make up water treatment plants (WTP), as well as investigate factors influencing on their removal. Some selectivity in the removal of these microorganisms can cause a harmful scenario in which toxic strains are present in product water. There is a certain tendency among experts to consider morphological characteristics as factors influencing the removal of these organisms in WTP. However, there is a lack of in-depth studies on this issue. In this study, we examine the influence of cyanobacterial morphology on their removal efficiencies in two WTP with distinct water treatment technologies (WTP1 - Direct Filtration; WTP2 - Direct Double Filtration), as well as investigate the effect of unit operation on trichomes integrity of these abovementioned organisms, in WTP1, 2 and a Pilot Plant. The least removed genera in WTP1 were Geitlerinema and Dolichospermum, both with an average removal of 68.4%. While for the WTP2, were Coelomoron and Pseudanabaena with 95.9% and 97.8%, respectively. There were significant differences between the average removals of filamentous cyanobacteria (FC) and colonial only in WTP2. The FC seem to be better removed than colonies. One verified that the dimentions of cyanobacteria did not influence on removal efficiency of these organisms. Among all WTP, the upflow filter of WTP2 were the unique to possess interstitial spaces smaller than lager cyanobacteria, leading to a positive correlation between percentage of cell lost and length of trichomes. Contrary to what was assumed, there were no correlation between trichome breakage and removal efficiency in studied WTP. The structure “mucilaginous sheath + short trichome” seems to be a promoter configuration to protect cyanobacteria against breakage throughout the whole treatment process. Further studies are needed in order to better understand the factors influencing the removal of cyanobacteria in these and other treatment technologies.